IMPROVEMENT OF LEGISLATION IN THE SPHERE OF THE STATE-PRIVATE PARTNERSHIP - P. Zubakha (Вестник университета)
This article is devoted to the analysis of legislation in the field of public-private partnership (PPP). The article substantiates the importance of an effective regulatory and legal framework for the development of PPP in Russia. A negative evaluation of this normative and legal framework from point of view of market participants was revealed. The analysis of the main regulatory and legal framework in the sphere of implementation of public-private partnership projects is carried out. Deficiencies were found in the current drafts of the law on concession and the law on PPP. Recommendations are proposed to eliminate these shortcomings and increase the effectiveness of legislation in the field of public-private partnership.